AMF colonization affects allelopathic effects of Zea mays L. root exudates and community structure of rhizosphere bacteria - Ma, Junqing; Xie, Yi; Yang, Yisen; Jing, Changliang; You, Xiangwei; Yang, Juan; Sun, Chenyu; Qin, Shengfeng; Chen, Jianhua; Cao, Kexin; Huang, Jinghua; Li, Yiqiang (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) widely exist in the soil ecosystem. It has been confirmed that AMF can affect the root exudates of the host, but the chain reaction effect of changes in the root exudates has not been reported much. The change of soil microorganisms and soil enzyme vigor is a direct response to the change in the soil environment. Root exudates are an important carbon source for soil microorganisms. AMF colonization affects root exudates, which is bound to have a certain impact on soil microorganisms. This manuscript measured and analyzed the changes in root exudates and allelopathic effects of root exudates of maize after AMF colonization, as well as the enzymatic vigor and bacterial diversity of maize rhizosphere soil. The results showed that after AMF colonization, the contents of 35 compounds in maize root exudates were significantly different. The root exudates of maize can inhibit the seed germination and seedling growth of recipient plants, and AMF colonization can alleviate this situation. After AMF colonization, the comprehensive allelopathy indexes of maize root exudates on the growth of radish, cucumber, lettuce, pepper, and ryegrass seedlings decreased by 60.99%, 70.19%, 80.83%, 36.26% and 57.15% respectively. The root exudates of maize can inhibit the growth of the mycelia of the pathogens of soil-borne diseases, and AMF colonization can strengthen this situation. The results of enzymatic vigor and bacterial diversity in maize rhizosphere soil showed that after AMF colonization, the activities of dehydrogenase, sucrase, cellulase, polyphenol oxidase and neutral protein in maize rhizosphere soil increased significantly, while the bacterial diversity decreased but the bacterial abundance increased. This research can provide a theoretical basis for AMF to improve the stubble of maize and the intercropping mode between maize and other plants, and can also provide a reference for AMF to prevent soil-borne diseases in maize.